A distribution network reconfiguration based on PSO: considering DGs sizing and allocation evaluation for voltage profile improvement - Mohd Nasir, Mohamad Na'im; Shahrin, Nor Mazura; Bohari, Zul Hasrizal; Sulaima, Mohamad Fani; Hassan, Mohammad Yusri (2014)
The optimized network reconfiguration and Distributed Generations (DG) sizing with allocation instantaneously via Particle Swarm Optimization (PSO) proposed a new way of allocation DG based on low voltage profile. This method consists of three steps. It started with categorized the switching sequences for radial network configuration while observe the P losses and the profile of voltage without DG. The second step is reconfiguration feeder for reduce losses via DGs allocation based on substations geographical location. The final step is sizing and allocation DGs at each bus with low voltage profile produced from the first step, used to mend the voltage profile and minimize the Plosses also compared the result with the geographical based allocation results. The objective of this study is to mend the voltage profile while decreasing the Plosses by using optimization technique considering network reconfiguration, DGs Sizing and allocation concurrently. Four cases are compared which is case 1 is the initial case and taken as a reference. All three stages are tested on standards IEEE 33 bus system by using Particle Swarm Optimization (PSO) technique in MATLAB software. This method proved that improvement of Plosses and voltage profile has been made by change of the switching topology with DGs sizing and allocation technique respectively.